Academic Health Centers' configurations, scientific productivity, and impact: Insights from the Italian setting. Issue 12 (December 2022) - D'Aniello, Luca; Spano, Maria; Cuccurullo, Corrado; Aria, Massimo
Highlights: AHCs' organizational configurations by considering their structural and operational features were identified. AHCs configurations' influence on scientific productivity, research impact, and growth was measured. No study analyzes different AHCs configurations that influence productivity and scientific impact. Abstract: Academic Health Centers (AHCs) have an enormous impact on health, society, and national competitiveness. They have a threefold strategic mission and heterogeneous models of governance. Our aim is to investigate how different AHC configurations are associated with research performance. The method we adopted follows two steps. First, we identify organizational configurations through cluster analysis of nine variables. Second, we correlate these configurations to bibliometric measures of research outputs. Findings show that AHCs, that are specialty-focused and not mainly involved in educational activities are more productive and have more research impact than fully integrated and affiliated AHCs. Those AHCs also share secondary contextual features.